The McGraw-Hill guide to English literature - Lawrence, Karen (McGraw-Hill, 1985)
The bok cové the poets of the preromantic and romantic periods, from William Blake to John Keats, major poets, essayists and novelists of Victorian England, including such figures as Tennyson, Dickens and the Brontes, etc.